2018
DOI: 10.1007/s00406-018-0937-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity as a risk factor for mortality in people with anorexia nervosa

Abstract: Anorexia nervosa (AN) is found associated with increased mortality. Frequent comorbidities of AN include substance use disorders (SUD), affective disorders (AD) and personality disorders (PD). We investigated the influence of these psychiatric comorbidities on all-cause mortality with demographic and socioeconomic factors considered as confounders in the observation window between January 2007 and March 2016 for 1970 people with AN, using data from the case register of the South London and Maudsley (SLaM) NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 65 publications
(78 reference statements)
6
42
1
1
Order By: Relevance
“…In users of secondary mental healthcare services an SMR of 5.2 (95% confidence interval (CI): 3.8–7.0) was reported for anorexia nervosa and atypical anorexia nervosa according to ICD-10 criteria [ 16 ]. Also using ICD-10 criteria, Suokas et al found a hazard ratio of 6.5 (95% CI: 3.5–12.3) for people with anorexia nervosa and atypical anorexia nervosa treated in tertiary care [ 17 ].…”
Section: Global Burden Of Disease Studymentioning
confidence: 99%
“…In users of secondary mental healthcare services an SMR of 5.2 (95% confidence interval (CI): 3.8–7.0) was reported for anorexia nervosa and atypical anorexia nervosa according to ICD-10 criteria [ 16 ]. Also using ICD-10 criteria, Suokas et al found a hazard ratio of 6.5 (95% CI: 3.5–12.3) for people with anorexia nervosa and atypical anorexia nervosa treated in tertiary care [ 17 ].…”
Section: Global Burden Of Disease Studymentioning
confidence: 99%
“…Eating disorders (ED) include a variety of diagnoses such as anorexia nervosa (AN), bulimia nervosa (BN), and eating disorder otherwise not specified (EDNOS) (American Psychiatrist Association [APA], ). ED patients have high rates of mortality with psychiatric comorbidity contributing to these elevated rates (Himmerich et al , Himmerich et al ). They are more likely to present to hospital with self‐harm (Perez, Marco, & Canabate, ; Smithuis et al, ) or a suicide attempt (Suokas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…End-of-treatment remission rates of RCTs in adult patients with AN range between 13 and 43% [12]. This is a sobering figure highlighting the pernicious nature of AN and its mortality rate, which is-as already mentioned above-five to six times greater than in the general population [6,13,14].…”
Section: Psychopharmacological Treatment For Anorexia Nervosamentioning
confidence: 91%
“…A recent longitudinal cohort study showed that only about 30% of patients with AN have recovered after 9 years [5]. AN has also been reported to be associated with a significantly increased mortality with a standardized mortality ratio (SMR) of 5.21 [6]. Thus, novel approaches such as psychopharmacological options should be considered to improve the treatment outcome and the care for people with AN.…”
Section: Introduction 11 Anorexia Nervosamentioning
confidence: 99%